PENINGKATAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MENGGAMBAR DENGAN BENTUK GEOMETRI DI TKIT ADZKIA V KOTA PADANG - Tesya cahyani Kusuma; Yeni Rahman (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
The purpose of this research is to increase children's creativity through drawing activities with geometric shapes. This research was conducted with a total of 16 children. This type of research is in the form of classroom action research (CAR). Data collection techniques are observation and documentation sheets. This study has four components, namely planning, implementation, observation and reflection. This study consisted of two cycles, namely cycle I and cycle II, each cycle was carried out in five times. The results of the study were from pre-action and in each cycle showed an increase in children's creativity in drawing with geometric shapes, at pre-action 58.4% increased the first cycle with the results of 67.74% and continued into the second cycle an increase with the result of 81.06%. And in beam building activities, at the pre-action 58.8% there was an increase in the first cycle with the results of 68.58% and continuing to the second cycle an increase with the results of 82.34%.